Creatine-electrolyte supplementation improves repeated sprint cycling performance: A double blind randomized control study - Daniel L. Crisafulli; Harsh H. Buddhadev; Lorrie R. Brilla; Gordon R. Chalmers; David N. Suprak; Jun G. San Juan (Taylor & Francis Group, 2018)
Background Creatine supplementation is recommended as an ergogenic aid to improve repeated sprint cycling performance. Furthermore, creatine uptake is increased in the presence of electrolytes. Prior research examining the effect of a creatine-electrolyte (CE) supplement on repeated sprint cycling performance, however, did not show post-supplementation improvement. The purpose of this double blind randomized control study was to investigate the effect of a six-week CE supplementation intervention on overall and repeated peak and mean power output during repeated cycling sprints with recovery periods of 2 min between sprints. Methods Peak and mean power generated by 23 male recreational cyclists (CE group: n = 12; 24.0 ± 4.2 years; placebo (P) group: n = 11; 23.3 ± 3.1 years) were measured on a Velotron ergometer as they completed five 15-s cycling sprints, with 2 min of recovery between sprints, pre- and post-supplementation. Mixed-model ANOVAs were used for statistical analyses. Results A supplement-time interaction showed a 4% increase in overall peak power (pre: 734 ± 75 W; post: 765 ± 71 W; p = 0.040; ηp 2 = 0.187) and a 5% increase in overall mean power (pre: 586 ± 72 W; post: 615 ± 74 W; p = 0.019; ηp 2 = 0.234) from pre- to post-supplementation for the CE group. For the P group, no differences were observed in overall peak (pre: 768 ± 95 W; post: 772 ± 108 W; p = 0.735) and overall mean power (pre: 638 ± 77 W; post: 643 ± 92 W; p = 0.435) from pre- to post-testing. For repeated sprint analysis, peak (pre: 737 ± 88 W; post: 767 ± 92 W; p = 0.002; ηp 2 = 0.380) and mean (pre: 650 ± 92 W; post: 694 ± 87 W; p < 0.001; ηp 2 = 0.578) power output were significantly increased only in the first sprint effort in CE group from pre- to post-supplementation testing. For the P group, no differences were observed for repeated sprint performance. Conclusion A CE supplement improves overall and repeated short duration sprint cycling performance when sprints are interspersed with adequate recovery periods.